2019
DOI: 10.1002/jctb.5956
|View full text |Cite
|
Sign up to set email alerts
|

2‐Deoxyribose‐5‐phosphate aldolase from Thermotoga maritima in the synthesis of a statin side‐chain precursor: characterization, modeling and optimization

Abstract: BACKGROUND Producing statin side‐chains by sequential aldol condensation catalyzed by 2‐deoxyribose‐5‐phosphate aldolase (DERA) (EC 4.1.2.4) is the best‐known and most promising synthetic route. The advantage of this process is the formation of two stereocenters in a single step starting from inexpensive achiral components, acetaldehyde and chloroacetaldehyde. The limitation for the industrial‐scale application is enzyme inactivation caused by substrates as well by the intermediate produced by single aldol add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…DERA activity assay : The hydrolysis activity of Pa DERA N‐His and Pa DERA C‐His AA C49M was determined measuring the oxidation of NADH as described previously [37] . The assay mixture contained 100 mM KPi buffer pH 7, 0.2 mM NADH, 0.4 mM DR5P, 4 μL of α‐glycerophosphate dehydrogenase/triosephosphate isomerase mixture (α‐GDH‐TPI) and 5 μL of freshly purified DERA, in a final volume of 0.5 mL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DERA activity assay : The hydrolysis activity of Pa DERA N‐His and Pa DERA C‐His AA C49M was determined measuring the oxidation of NADH as described previously [37] . The assay mixture contained 100 mM KPi buffer pH 7, 0.2 mM NADH, 0.4 mM DR5P, 4 μL of α‐glycerophosphate dehydrogenase/triosephosphate isomerase mixture (α‐GDH‐TPI) and 5 μL of freshly purified DERA, in a final volume of 0.5 mL.…”
Section: Methodsmentioning
confidence: 99%
“…The hydrolysis activity of PaDERA N-His and PaDERA C-His AA C49M was determined measuring the oxidation of NADH as described previously. [37] The assay mixture contained 100 mM KPi buffer pH 7, 0.2 mM NADH, 0.4 mM DR5P, 4 μL of αglycerophosphate dehydrogenase/triosephosphate isomerase mixture (α-GDH-TPI) and 5 μL of freshly purified DERA, in a final volume of 0.5 mL. The reaction was initiated by the addition of DERA and the subsequent decrease of NADH concentration was monitored at 340 nm for 1 min at 28 °C with continuous shaking.…”
Section: Dera Activity Assaymentioning
confidence: 99%
“…Please note that we omitted to write out the equations for the second element of the output vector u 2 for model M 1 and model M 2 due to readability reasons. However, keep in mind that the functions F 1 and F 2 in Equations (22) and (23) differ. The inverse model (Equation (22)) with its flat output (Equation (21)) satisfies the set containing all three conditions for differential flatness (Equations (4)-(6)).…”
Section: Differential Flatness Propertymentioning
confidence: 99%
“…However, biocatalytic production of the related bulk and fine chemicals and active pharmaceutical ingredients (APIs) is insufficiently explored today. Therefore, the application of enzymes in organic synthesis is currently an important research topic to exploit the significant potential of improving manufacturing processes in the chemical and pharmaceutical industry under the agenda of green chemistry [23,24]. An essential problem with all mathematical models and model-based design concepts, including MBDoE, is the uncertainty in model parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The data concerning aldolase-catalysed reactions is scarce 53,84,85 , and for now, only two research papers report mathematical modelling of the reaction towards statin side-chain production. 53,86 Švarc et al 86 have reported a mathematical model (consisting of a formal kinetic model that includes the data-driven or the empirical model that has less kinetic constants) validated in multiple reactor configurations. Using the developed model, process simulations were done and optimal process design was pro-posed.…”
Section: Statins and Statin Precursorsmentioning
confidence: 99%